Left-right asymmetries in polarized e-mu scattering - Montero, J. C. [UNESP]; Pleitez, V. [UNESP]; Rodriguez, M. C. [UNESP] (American Physical Soc, 1998)
We consider, in the electroweak standard model context, several left-right asymmetries in μe elastic scattering at fixed target and collider experiments. For the former case, we show that the muon mass effects are important in a wide energy range. We also show that these asymmetries are sensitive to the electroweak mixing angle θW. The effect of an extra Z' neutral vector boson appearing in a 3-3-1 model is also considered. The capabilities of these asymmetries in the search of this extra Z' are addressed.